2019
DOI: 10.1007/s12028-019-00695-7
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Regional Brain Monitoring of Tissue Ischemia in Severe Cerebral Venous Sinus Thrombosis

Abstract: Background: Comatose critically ill patients with severe diffuse cerebral venous thrombosis (CVT) are at high risk of secondary hypoxic/ischemic insults, which may considerably worsen neurological recovery. Multimodal brain monitoring (MBM) may therefore improve patient care in this setting, yet no data are available in the literature. Methods: We report two patients with coma following severe diffuse CVT who underwent emergent invasive MBM with intracranial pressure (ICP), brain tissue oximetry (PbtO 2), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…As with our study, the International Study on Cerebral Vein and Dural Sinus Thrombosis [2] found that 17.1% patients had thrombosis of concomitant cortical veins along with major sinuses, a result supported by others [3,[9][10][11][12]. Although we do not evaluate the pathophysiological basis of CVT coma, it seems that age [13] and thrombosis of SSS [10,11,14] may lead to the higher occurrence of coma in men due to impaired venous drainage and cerebrospinal fluid reabsorption, causing cytotoxic oedema, herniation, and diminished cerebral perfusion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As with our study, the International Study on Cerebral Vein and Dural Sinus Thrombosis [2] found that 17.1% patients had thrombosis of concomitant cortical veins along with major sinuses, a result supported by others [3,[9][10][11][12]. Although we do not evaluate the pathophysiological basis of CVT coma, it seems that age [13] and thrombosis of SSS [10,11,14] may lead to the higher occurrence of coma in men due to impaired venous drainage and cerebrospinal fluid reabsorption, causing cytotoxic oedema, herniation, and diminished cerebral perfusion.…”
Section: Discussionsupporting
confidence: 89%
“…This study is the first report that transverse sinus thrombosis is significantly less likely to cause coma, possibly because it primarily affects the posterior parts of the brain and has a more localized impact, leading to slow onset thrombosis and less widespread neurological damage in the presence of collateral venous drainage [10–12]. In contrast, the SSS drains a more extensive area of the cerebral hemispheres, including motor areas, causing rapid and profound neurological impairment leading to coma in SSS thrombosis [11, 14, 15].…”
Section: Discussionmentioning
confidence: 99%